Maharah Qira'ah Learning Strategy for Integrated Islamic Elementary School (SDIT) Students During Covid-19 Pandemic - Ritonga, Apri Wardana; Fitri, Aulia (Universitas Muhammadiyah Mataram, 2021)
The Covid-19 pandemic demands teachers to develop strategies for learning maharah qira'ah well. So that learning has a good impact on the development of student skills. This study aims to describe the maharah qira'ah learning strategy carried out by teachers during the Covid-19 pandemic era. This study used a qualitative approach with the case study method at SDIT Nurul Ikhlas Padang, while data collection was through observation, interviews and document study. The data were analyzed using triangulation of data and data sources, while the data validation stage used Miles and Huberman's theory, namely reducing data, presenting data and verification. This study shows that the maharah qira'ah learning strategy in the pandemic era was carried out using the electronic media Whatsapp, Google Classroom and Youtube through full mentoring from the teacher. This study recommends further research to test the effectiveness of learning maharah qira'ah using online media for elementary school students.